A brief history of TOR. (22nd March 2011) - Loewith, Robbie
Abstract : The TOR (target of rapamycin) serine/threonine kinases are fascinating in that they influence many different aspects of eukaryote physiology including processes often dysregulated in disease. Beginning with the initial characterization of rapamycin as an antifungal agent, studies with yeast have contributed greatly to our understanding of the molecular pathways in which TORs operate. Recently, building on advances in quantitative MS, the rapamycin-dependent phosphoproteome in the budding yeast Saccharomyces cerevisiae was elucidated. These studies emphasize the central importance of TOR and highlight its many previously unrecognized functions. One of these, the regulation of intermediary metabolism, is discussed.